Cloning and expression of the gene from Candida albicans that encodes a high-affinity corticosteroid-binding protein. - Malloy, P J (1993)
We have previously demonstrated the presence of a corticosteroid-binding protein (CBP) in Candida albicans and speculated on its homology to the glucocorticoid receptor. To explore this relationship further, we cloned the CBP gene. Our strategy employed sequencing enzymatically derived peptide fragments from purified CBP and using this information to synthesize degenerate oligonucleotide primers for use in the PCR. A 117-bp fragment amplified from C. albicans DNA was then used to screen a genomic library. Hybridizing clones were isolated, and DNA sequencing revealed an open reading frame of 1467 bp which encoded a protein with a molecular weight of 55,545. Southern analysis demonstrated that the gene was present at a unique locus within chromosome R of the Candida genome, while Northern analysis showed that the gene was expressed in C. albicans as a 1.8-kb transcript. CBP was over-expressed in Saccharomyces cerevisiae, and it exhibited an apparent dissociation constant (Kd) of 7 nM for [3H]corticosterone and displayed a steroid hormone binding profile comparable to that of the native protein. Searches of the data banks revealed little overall similarity to other cloned genes. However, the amino acid sequence contains a dinucleotide-binding fingerprint. In conclusion, we have cloned the gene encoding the CBP from C. albicans and have shown that the expressed protein has the properties of the native CBP. A comparison of the cloned gene to members of the steroid-thyroid-retinoic acid receptor gene superfamily showed that CBP is unrelated to these hormone receptors.